Каждый за себя: [роман] / Александра Маринина - Маринина Александра Борисовна (Эксмо, 2003)
Экземпляры: ФО-7 (201402) / Инвентарный номер: 48968 / Цена: 100.00 / Сис.шифр: Р2 / Авт.знак: М 26 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6